دراسة تجريبية لتقصي تأثير الدروز على الخواص الميكانيكية للعظام القحفية - خليل, عبد الكريم; خفيف, خضر; عطية, أمجد (Latakia University Journal -Medical Sciences Series, 2019)
Cranial sutures are essential components in the cranio-facial skeleton, so it is important to understand their general influence on the biomechanical behavior of this skeleton. This study aims to compare between cranial bones containing sutures and those not containing sutures regarding bending stress, and study the relationship between bending stress and interdigitation index and compact bone ratio. This study was conducted using bone samples taken from fresh skulls of male sheep. 67 bone samples were divided into three groups: bone samples not containing sutures, bone samples containing straight-edged sutures, bone samples containing interdigited sutures. The bone samples were loaded in general test machine, found in materials strength laboratory, Tishreen University, Lattakia, Syria. The samples were loaded as beams in three point bending test to calculate the bending stress. We also calculated interdigitation index and compact bone ratio. We found that mechanical properties of cranial sutures increase with interdigitation, and don`t correlate with compact bone ratio. Cranial bones containing high-interdigitated sutures have bending strength (bending stress) close to what pure cranial bones have. تعتبر الدروز القحفية من العناصر الأساسية في المركب القحفي الوجهي, لذلك من الضروري فهم التأثير العام لهذه الدروز على السلوك الميكانيكي الحيوي لهذا المركب. يهدف هذا البحث إلى المقارنة بين القطع العظمية القحفية التي تحوي دروز وبين العظام القحفية الخالية من الدروز فيما يخص إجهاد الانحناء ودراسة العلاقة بين إجهاد الانحناء لهذه العينات وكل من مؤشر التشابك ونسبة العظم القشري فيها. أجريت هذه الدراسة التجريبية على عينات عظمية مأخوذة من جماجم حديثة لذكور الخراف, حيث شملت 67 عينة عظمية قسمت إلى ثلاث مجموعات: عينات عظمية لا تحتوي دروز, عينات عظمية تحوي دروز مسطحة, وعينات عظمية تحوي دروز متشابكة. جرى تحميل هذه العينات في آلة الاختبارات العامة في مخبر مقاومة المواد في كلية الهندسة الميكانيكية والكهربائية, جامعة تشرين. استخدمت في اختبار الانحناء ثلاثي النقاط وذلك من أجل حساب إجهاد الانحناء. جرى كذلك حساب مؤشر التشابك ونسبة العظم القشري. أظهرت نتائج الدراسة أن الخواص الميكانيكية للدروز القحفية تزداد بازدياد درجة التشابك بين طرفيها, ولا ترتبط بنسبة العظم القشري في العظم المحيط بها, وأن العظام القحفية التي تحتوي على دروز عالية التشابك تمتلك مقاومة للانحناء (إجهاد الانحناء) قريبة من العظام القحفية التي لا تحوي دروز.